DIGITAL PAWN SERVICE AND FINANCIAL LITERACY: THE MEDIATING ROLE OF IT-ENABLED - Auji, Shonifah Dzikro; Safitri, Anita (Penerbit Lafadz Jaya, 2026)
Indonesia faces a financial inclusion-literacy paradox, with 80% inclusion versus 66% literacy per 2025 OJK SNLIK data, amid rapid FinTech growth including digital pawn services for micro-entrepreneurs. This study aims to examine financial literacy's mediating role between digital pawn service adoption and financial inclusion outcomes in emerging markets. Employing Systematic Literature Review (SLR) methodology per PRISMA 2020 guidelines, the population comprises peer-reviewed articles, proceedings, and grey literature (2021-2025) from Google Scholar, Scopus, and Web of Science, focusing on Indonesia/Southeast Asia. From initial searches, 45 studies were included after title/abstract screening, full-text review, and quality appraisal using quantitative/qualitative checklists. Data extraction covered study characteristics, findings, and effect sizes; thematic analysis and narrative synthesis via directed content analysis assessed mediation pathways. Results reveal financial literacy significantly mediates this relationship (indirect effect β=0.30, p<0.001 via SEM-PLS), amplifying direct adoption benefits like cost reduction (15-25%) and 31-38% higher account ownership, though trust deficits and regulatory gaps persist. In conclusion, policymakers must integrate literacy modules into platforms for sustainable inclusion, prioritizing OJK-led partnerships.